GAMBARAN BUKTI MEDIS KASUS KEJAHATAN SEKSUAL YANG DIPERIKSA DI BAGIAN ILMU KEDOKTERAN FORENSIK RSUP SANGLAH PERIODE JANUARI 2009 – DESEMBER 2013 - Kartika Wijaya, Cecilia (E-Jurnal Medika Udayana, 2017)
High sex drive can push someone to commit sexual assault to fulfill their need. Generally, sexual assault happens around the world, and it tends to increase annually with diverse medical evidence. This study aims to discover the overview of medical evidence of sexual assault examined in Sanglah Hospital between 2009 and 2013. This study was a descriptive study with cross-sectional approach using clinical forensic data. The number of case which met the inclusion criteria was 291 cases. This study showed that the victims of sexual assault mostly came from teenage group, which were 175 cases (60.1%). Sixty six point three percent of victim had forensic medical examination after 72 hours had passed, 26.1% were examined within 72 hours of the assault, and 7.6 % were not found any sign of sexual intercourse. The physical examination of the victim found that most cases indicating that there were not any sign of physical abuse, as many as 85.2%. The sign of sexual intercourse found in most cases was penetration without positive ejaculation sign, as many as 78%. Eighty seven point six percent of cases did not affect the victim’s life, but some victims got pregnant and suffered psychiatric disorder, 10.7% and 1.7% respectively. Keyword s : Sexual assault , forensic, medical evidence .